Size exclusion chromatography (SEC) - Peukert, Wolfgang; Kaspereit, Malte; Hofe, Thorsten; Gromotka, Lukas (Particle Separation Techniques, 2022)
Size exclusion chromatography (SEC) is a liquid phase chromatographic technique for separating molecules, proteins, macromolecules, and nanoparticles (below 100 nm) solely according to their hydrodynamic volume in solution. Classification depends on the size- and shape-dependent exclusion of components in the pores of the stationary phase material, that is, larger and less mobile components leave the column first. Ideally, the separation is purely driven by entropy, the absence of strong enthalpic interactions encompasses mild operating conditions. SEC is a standard method in polymer science and technology for the characterization of molecular weight distributions. SEC is also well established for preparative applications, for example, for the separation of proteins from aggregates in biotechnology. The size-dependent classification of nanoparticles is a promising new field of application.<br